Pemberian Antibiotika Rasional pada Infeksi Mata - Winarto Winarto (RSUP Dr. Kariadi, 2015)
Eye and adnexal infection has clinical range from mild infection without visual acuity disturbances up to severe infection in which an emergency cases could end with blindness. Antibiotics has a central role in treatment of eye infections, therefore should be given rationally. Rational of basic principles of infection management consist of identification of causing microbes, sensitivity test to antibiotics and choosing a prompt antibiotics based on pharmacokinetics and pharmacodynamics given to the patient at the right dose, right route, appropiate time and affordable by the patients. Previous data concerning etiologic agent and pattern of sensitivity to antibiotics were considered when give an empiric treatment, therefore theese data should be published to clinicians regularly. The part of the eye which diffcult to be reached by immune system, it is advisable to choose a bactericidal antibiotics rather than bacteriostatic, e.g. keratitis, corneal ulcer and endophthalmitis. Toxic effects to the corneal epithelium and retinal cell should be bear in mind in order to treat eye infections to obtain best results.